2022
DOI: 10.1073/pnas.2201646119
|View full text |Cite
|
Sign up to set email alerts
|

Acat1/Soat1 knockout extends the mutant Npc1 mouse lifespan and ameliorates functional deficiencies in multiple organelles of mutant cells

Abstract: Significance Niemann-Pick type C disease (NPCD) is an incurable genetic neurological disorder. Cells with NPC mutations fail to export cholesterol from endosomal organelle to multiple other organelles. ACAT1 is an enzyme that converts cholesterol to cholesteryl esters for storage. In mutant NPC cells, cholesterol storage still occurs, although at reduced rate. Here we show that in mutant NPC cells, ACAT1 blockade (A1B) decreases cholesterol storage such that it can be utilized to fulfill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…It is known that after LPS stimulation, a portion of TLR4 is enriched at the caveolae/lipid rafts region of the PM [ 40 ]. In mouse embryonic fibroblast cells, A1B causes cholesterol translocation from the ER where ACAT1/SOAT1 resides to various membrane organelles, including the trans-Golgi network (TGN) and various other membrane organelles [ 41 ]. In the current cell system, we suspect that pre-treating cells with A1B may affect the intracellular distribution of TLR4, especially upon LPS stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that after LPS stimulation, a portion of TLR4 is enriched at the caveolae/lipid rafts region of the PM [ 40 ]. In mouse embryonic fibroblast cells, A1B causes cholesterol translocation from the ER where ACAT1/SOAT1 resides to various membrane organelles, including the trans-Golgi network (TGN) and various other membrane organelles [ 41 ]. In the current cell system, we suspect that pre-treating cells with A1B may affect the intracellular distribution of TLR4, especially upon LPS stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…The ACAT1/SOAT1 blockade has also been shown to enhance HMG-CoA reductase degradation by increasing levels of 24S-hydroxycholesterol [ 58 ] and suppress neuroinflammation by altering toll-like receptor 4 (TLR4) trafficking and activation [ 86 ]. Additionally, in a mouse model, genetic inactivation of ACAT1/SOAT1 was recently shown to benefit a rare pediatric neurodegenerative disease, Niemann-Pick type C1 (NPC1) [ 87 ]. The effects of ACAT1/SOAT1 inhibition are undoubtedly beneficial in disease contexts, but it is difficult to tie these results together with a single common thread.…”
Section: Discussionmentioning
confidence: 99%
“…ACATs/SOATs are potential targets to treat several human diseases, including atherosclerosis [29], certain forms of cancer {early literature reviewed in [5]}, [30], and neurodegenerative diseases that include AD [31] and NPCD [32]. There are two Acats/Soats in mammals [4].…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 2, 2022. ; https://doi.org/10.1101/2022.08.30.505911 doi: bioRxiv preprint reported that in mouse embryonic fibroblast cells, A1B causes redistribution of cholesterol contents in multiple cellular compartments [32]. Thus, A1B could alter the cholesterol content of the TLR4 associated membrane microdomain at the PM and causes this domain to undergo caveolae-mediated endocytoses at a more rapid rate.…”
Section: Discussionmentioning
confidence: 99%